Teaching Soft Skills and Basic Mathematical Operations to SDN Kedungmlati Students Using the PERIODIK Teaching Aid - Tita Tengku Malinda; Fida Roudlotul Jannah; Lia Budi Tristanti; Amelia Eka Pratiwi; Ifa Rochma Wati (Institute for Research and Community Services, 2022)
SDN Kedungmlati is the only public elementary school in Kedungmlati village. The school lacks the infrastructure to support the teaching and learning process. They do not have adequate teaching aids to help the students learn abstract concepts in mathematics. We carried out this community service to introduce the PERIODIK teaching aid to respond to their needs. PERIODIK teaching aids are aids in learning basic mathematical operations, which include addition, subtraction, multiplication, and division of integers. This activity, conducted in the academic year of 2019/2020, aimed to increase the students' soft skills in using the PERIODIK teaching aid and thus develop their understanding of basic mathematical operations. The soft skills we expected the students to gain include the skills to use the teaching aid, be persistent, and be able to cooperate with others. This activity was carried out in three stages: preparation, implementation, and reporting, and evaluated using two instruments: a questionnaire and a written test. The questionnaire was distributed to the students before and after the training, whereas the written test was conducted only at the end of the activity. We used paired samples t-test to measure the students’ soft skills and independent samples t-test to examine whether the students had reached achieved the minimum score of 80. The results show that teaching aids can improve students' soft skills and understanding of the four basic mathematical operations. The PERIODIK then became an inventory of SDN Kedungmlati for learning mathematics.